2013
DOI: 10.1093/jjco/hyt075
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia Pathophysiology and Translational Aspect of Herbal Medicine

Abstract: About half of all cancer patients show a syndrome of cachexia, characterized by anorexia and loss of adipose tissue and skeletal muscle mass. Numerous cytokines have been postulated to play a role in the etiology of cancer cachexia. Cytokines can elicit effects that mimic leptin signaling and suppress orexigenic ghrelin and neuropeptide Y signaling, inducing sustained anorexia and cachexia not accompanied by the usual compensatory response. Furthermore, cytokines have been implicated in the induction of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 113 publications
(145 reference statements)
0
22
0
1
Order By: Relevance
“…These inputs are transduced into neuronal responses and, via signaling pathways, behavioral responses. Current evidence suggests that systemic inflammation plays a critical role in inducing cancer anorexia by triggering a complex neurochemical cascade (Laviano et al, 2003; Fearon et al, 2013; Suzuki et al, 2013; Tuca et al, 2013). Increased cytokine expression from tumor growth prevents the hypothalamus from responding appropriately to peripheral signals by persistent stimulation of anorexigenic pathways and inhibition of orexigenic pathways (Suzuki et al, 2013; Tuca et al, 2013).…”
Section: Mechanisms Of Cancer Cachexiamentioning
confidence: 99%
“…These inputs are transduced into neuronal responses and, via signaling pathways, behavioral responses. Current evidence suggests that systemic inflammation plays a critical role in inducing cancer anorexia by triggering a complex neurochemical cascade (Laviano et al, 2003; Fearon et al, 2013; Suzuki et al, 2013; Tuca et al, 2013). Increased cytokine expression from tumor growth prevents the hypothalamus from responding appropriately to peripheral signals by persistent stimulation of anorexigenic pathways and inhibition of orexigenic pathways (Suzuki et al, 2013; Tuca et al, 2013).…”
Section: Mechanisms Of Cancer Cachexiamentioning
confidence: 99%
“…Anorexia and hypercatabolism have been found in cachectic patients to be driven by mechanical factors such as cytokines, circulating hormones, neuropeptides, neurotransmiters, and tumor-derived factors. Recent studies have also identiied other processes that potentially contributed to the pathophysiology of pancreatic cancer cachexia, including neural invasion and abnormalities in muscle microenvironment [20][21][22][23][24][25]. The following section will review these currently proposed mechanisms that interact and contribute to the development of this disease.…”
Section: Mechanisms Of Cancer Cachexiamentioning
confidence: 99%
“…In some animal and clinical studies, leptin levels were found to not be elevated in tumor-bearing rats and patients with cancer cachexia [38][39][40][41]. Recent research demonstrated that in cancer cachexia, IL-1 and TNF-α mimic leptin signaling and result in the interference of the orexigenic pathway, which is normally a response to reduced leptin levels [24,42]. This suggests that even during starvation, the inhibition of the orexigenic response and activation of the anorexigenic pathway can occur and lead to unopposed anorexia and elevated energy expenditure.…”
Section: Centrally Mediated Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations